Publisher Correction: Quantum mechanics: An inconsistent friend. Issue 11 (November 2018) - Pusey, Matthew
In the version of this News & Views originally published, the link for ref. 7 was incorrectly given as https://arxiv.org/abs/1604.07422; it should have been https://scirate.com/arxiv/1604.07422. This has now been corrected.